Thermal Strain During Open-Water Swimming Competition in Warm Water Environments - Chalmers, Samuel; Shaw, Gregory; Mujika, Iñigo; Jay, Ollie (Frontiers in Physiology, 2021)
Open-water swim racing in warm water is associated with significant physiological strain. However, existing international policy that governs safe participation during competition relies only on a fixed water temperature threshold for event cancellation and has an unclear biophysical rationale. The current policy does not factor other environmental factors or race distance, nor provide a stratification of risk (low, moderate, high, or extreme) prior to the threshold for cancellation. Therefore, the primary aim of this Perspectives article is to highlight considerations for the development of modernized warm-water competition policies. We highlight current accounts (or lack thereof) of thermal strain, cooling interventions, and performance in warm-water swimming and opportunities for advancement of knowledge. Further work is needed that systematically evaluate real-world thermal strain and performance during warm water competition (alongside reports of environmental conditions), novel preparatory strategies, and in-race cooling strategies. This could ultimately form a basis for future development of modernized policies for athlete cohorts that stratifies risk and mitigation strategies according to important environmental factors and race-specific factors (distance).